Patient-reported results of simultaneous direct anterior approach and posterolateral approach total hip arthroplasties performed in the same patients - Zhi Yang (SpringerOpen, 2021)
Abstract Background Several studies have compared clinical results of the direct anterior approach (DAA) and the posterolateral approach (PLA) in total hip arthroplasty (THA); however, the effect of the surgical approach on outcome of THA remains controversial. Most of these studies used two distinct groups of patients, and THAs were performed by different surgeons, using different designs of prosthesis. These confounding factors may limit the strength of the conclusions. The purpose of this prospective, simultaneous bilateral randomized study was to investigate whether patients would perceive the difference between the direct anterior approach (DAA) and the posterolateral approach (PLA) after THA. Materials and methods Among 20 patients scheduled to undergo same-day bilateral THA between October 2017 and August 2019, one hip was randomly assigned to DAA and the other to PLA. Patient-reported outcome measures [Hip disability and Osteoarthritis Outcome Score (HOOS), patients’ hip pain on mobilization] and physician-assessed measures [Harris Hip Score (HHS), operative time, intraoperative blood loss, cup abduction, cup anteversion, stem orientation, and incidence of complications (intraoperative fracture, nerve damage, incisional problem, or postoperative dislocation)] were compared. Results All patients were followed up for 12 months. Hip pain was significantly less with DAA-THA compared with PLA-THA at postoperative 1, 3, and 7 days (p < 0.05). There was no clinical difference between DAA-THA and PLA-THA in terms of the VAS, HOOS, or HSS at 6 weeks and 3, 6, and 12 months postoperatively (p > 0.05). DAA-THA had a longer operative time and shorter length of incision compared with PLA-THA. There was no statistical difference between DAA-THA and PLA-THA in terms of intraoperative blood loss, cup abduction, cup anteversion, stem orientation, and perioperative complications (p > 0.05). Conclusions This study demonstrates that DAA-THA and PLA-THA could provide comparable HHS and HOOS at all follow-ups. Compared with PLA-THA, DAA-THA is associated with less hip pain within postoperative 7 days and shorter incision length, but longer operative time. Level of evidence Level I, therapeutic study. Trial registration Chinese Clinical Trail Registry, ChiCTR1800019816. Registered 30 November 2018—retrospectively registered, http://www.chictr.org.cn/showproj.aspx?proj=30863